Percutaneous pigtail catheter in the treatment of pneumothorax in major burns: The best alternative? Case report and review of literature. Issue 3 (May 2015) - Sebastian, Raul; Ghanem, Omar; Diroma, Frank; Milner, Stephen M.; Gerold, Kevin B.; Price, Leigh A.
Abstract Multiple factors place burn patients at a high risk of pneumothorax development. Currently, no specific recommendations for the management of pneumothorax in large total body surface area (TBSA) burn patients exist. We present a case of a major burn patient who developed pneumothorax after central line insertion. After the traditional large bore (24 Fr) chest tube failed to resolve the pneumothorax, the pneumothorax was ultimately managed by a percutaneous placed pigtail catheter thoracostomy placement and resulted in its complete resolution. We will review the current recommendations of pneumothorax treatment and will highlight on the use of pigtail catheters in pneumothorax management in burn patients.